(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Probiotics, defined by the World Health Organization (WHO) as live microorganisms that, when administered in adequate amounts, confer health benefits to the host, have gained attention for their role in maintaining oral health. They function by inhibiting pathogenic organisms, thereby enhancing resistance to harmful colonization and supporting metabolic activities. Aim: This study aims to evaluate the knowledge, practices, and attitudes toward probiotics among dental post-graduate students in Patna, with a focus on their awareness and perceived benefits for oral health. Study Design: A descriptive, cross-sectional survey was conducted among dental post-graduates from BIDSH, Patna, using a random sampling method. Data were analyzed using the chi-square test for statistical significance. Methodology: A structured questionnaire, comprising 24 items derived from existing literature on probiotic knowledge, was distributed to first-, second-, an third-year dental post-graduates. Results: Out of 105 participants, 63.81% were female and 36.19% were male. A substantial majority (96.14%) were aware of the term "probiotics," and 66.86% believed that probiotics could positively impact oral health. Conclusion: The study demonstrates a high level of awareness and knowledge about probiotics among dental post-graduate students in Patna. The positive perception of probiotics' role in oral health suggests the potential for incorporating probiotics into dental practice. Further community-based programs are recommended to explore their clinical implications for oral health improvement.